Harmonisasi Peraturan Daerah dengan Peraturan Perundang-Undangan Tingkat Pusat dalam Perspektif Negara Kesatuan - Aditya Sanjaya; Bintan R. Saragih; Hotma P. Sibuea; Gunawan Widjaja (LP3M Sekolah Tinggi Ilmu Hukum Al-Banna, 2025)
This study was motivated by the disharmony between central government regulations and local regulations (perda) in Indonesia. The study aims to analyze the forms and causes of disharmony, as well as to formulate ways to strengthen the harmonization mechanism within the framework of a unitary state. The method used is normative legal research with a legislative and conceptual approach, based on the study of primary and secondary legal materials. The results of the study show that the disharmony of local regulations is influenced by the ambiguity of the harmonization norms in the draft local regulations, the weak capacity of regional legislation, the dominance of local political interests, and the lack of vertical coordination between the central and regional governments. Therefore, it is necessary to affirm the norms and procedures for harmonizing draft local regulations, strengthen harmonization mechanisms (ex ante and ex post), conduct periodic evaluations, and optimize the role of relevant ministries/institutions and the Supreme Court to ensure the harmony of norms, certainty, justice, and the benefits of law.